(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2012)
This article proposes a bridge between an early and a late work of Gérard Genette, namely his article Frontières du récit and his collection of essays Fiction et diction. In Frontières du récit, Genette points at two instances of “anti-narrative” intrusion into narrative. The first is what Emile Benveniste called “discourse,” meaning the self-reflexive comments of the nar- rator, and the second is description, a mode of utterance that when found in a narrative, tem- porarily withholds the flow of the story. In the context of the proliferation of these instances in current narrative films and in the light of Genette’s observations in Fiction et diction, I will suggest that these anti-narrative elements provide us with a chance to fundamentally recon- sider the notion of narrative and to configure a paradigm shift in narratology, which Genette had already foreseen in his early work.